Enhancing Governance and Development: Analyzing Performance Management Practices - Winoto, Suhartono (Journal of Transformative Governance and Social Justice, 2025)
In the ever-evolving landscape of governance and development, understanding the nuances of performance management becomes paramount. This study explores the dynamics within Armstrong's performance management cycle in the Pamekasan Regency case, which sheds light on the dominant aspects and unveils opportunities for improvement. This research employs a qualitative approach through a case study method. At the same time, the data analysis is conducted utilizing QSR NVivo software to offer an in-depth exploration of performance management dynamics in the Pamekasan Regency. The findings of this study highlight the crucial significance of the planning phase within the performance management cycle of Pamekasan Regency. It reflects the steadfast commitment of the local government to articulate and pursue clear development plans. The set performance objective emerges as the most influential indicator, emphasizing the practical importance of well-defined objectives in guiding and evaluating development initiatives. The review phase follows closely with a commendable coefficient of about 77%. While the monitor phase shows the lowest score at 55%, this suggests that while the review phase performs well, attention and improvements are particularly needed in optimizing activities during the monitoring phase. Achieving a more holistic strategy will contribute to the overall effectiveness of Pamekasan Regency's performance management cycle.